2022
DOI: 10.3390/su14010551
|View full text |Cite
|
Sign up to set email alerts
|

Models of Sustainable Software: A Scoping Review

Abstract: Information and Communication Technologies (ICTs) play a double role in the strife for sustainable development goals, as both an enabler of green solutions and a cause of excessive consumption. While the primary focus of sustainability-related research is on the hardware aspect of ICT, its software aspect also deserves attention. In order for the notion of green and sustainable software to become widespread among practitioners, models are needed, both to be used as a reference on how to develop sustainable sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Numerous other authors [25][26][27][28][29][30][31] have also added to the conversation about sustainable software production. Their research examines several facets of sustainability in software engineering, from social responsibility and ethical considerations to energy efficiency and lowering environmental effects.…”
Section: Related Workmentioning
confidence: 99%
“…Numerous other authors [25][26][27][28][29][30][31] have also added to the conversation about sustainable software production. Their research examines several facets of sustainability in software engineering, from social responsibility and ethical considerations to energy efficiency and lowering environmental effects.…”
Section: Related Workmentioning
confidence: 99%
“…Swacha [19] provides an overview of SDLC models; they emphasize environmental friendliness and the sustainability of programmatic learning.…”
Section: Sdlc Modelsmentioning
confidence: 99%
“…The study concluded that sustainability was an emerging concern in software engineering and that there was a need for more research on the integration of sustainability into software development processes and products. We also observed that there are numerous models [32,33] related to sustainable software, which are primarily classified as software product models [34] and software development process models [35][36][37][38][39][40]. The Green Software Engineering (GSE) model [41,42] was developed by researchers at the University of Sannio in Italy and focuses on integrating environmental sustainability into software development processes.…”
Section: Related Workmentioning
confidence: 99%